IBRAHIM MOMINOV AS THE EDITOR-IN-CHIEF OF THE FIRST UZBEK CYCLOPAEDIA - Temur A. Mominov (International Scientific and Current Research Conferences, 2022)
This article analyzes the processes of the creation of the first Uzbek cyclopaedia, and the work of Ibrahim Mominov as its editor-in-chief regarding the creation of the cyclopaedia and his courage in founding the national school of cyclopaedia is highlighted.